Tafsir tematik: Berbuat kebajikan dalam perspektif al-Qur’an - Zumar, Yogi Ainuz (Maliki Interdisciplinary Journal, 2023)
This article examines the value of goodness from the perspective of the Qur’an through a thematic tafsit approach. From the study conducted on the virtue verses in the Qur’an, it can be seen that in doing good deeds, we are not differentiated by Allah, including in terms of gender, degree, position, etc. Unless you do it sincerely, sincerely, and achieve His pleasure. Thus, the value of kindness is so high in Islamic view, that we are invited to compete in doing good from children, teenagers, adults, to grandparents. Due to the importance of doing good, the Prophet said and invited humanity to hasten to do good before we could not make it at another time and finally without human knowledge our death was picked up. This study uses the method of thematic interpretation, analysis of descriptions of high-value virtue verses.